OPTIMALISASI LAHAN PEKARANGAN RUMAH DENGAN PENANAMAN BUAH-BUAHAN DI NAGARI SUNGAI KAMBUT, KABUPATEN DHARMASRAYA, PROVINSI SUMATERA BARAT - Muhammad Parikesit Wisnubroto; Edwin Edwin; Wulan Kumala Sari; Sri Heriza; Dewi Rezki; Zahlul Ikhsan; Dede Suhendra; Nike Karjunita; Halimatus Syahdia Hasibuan (Jurnal Abdi Insani, 2023)
Community service is important to do in order to develop the order and standard of living of the people in an area. One of them is in Nagari Sungai Kambut where many of the residents are not yet working or not working and some are only taking care of the household. In fact, when viewed from its natural potential, the Nagari Sungai Kambut region has quite a large potential for productive land, including the home yard. Therefore, dedication is carried out in the form of assistance in optimizing the use of the home yard for planting fruits. The hope is to increase the knowledge and improve the skills of the local population. The fruit produced can also be a source of income, apart from just for self-consumption. Service activities begin with socialization, counseling and followed by assistance in planting fruit trees. Farmers are guided and assisted by the team so that when there are problems they can be immediately resolved. During the socialization, the residents actively raised various questions, both from how to plant, maintain and even post-harvest. Seeing the enthusiastic response of the community shows that this service program has been able to increase knowledge about the importance of using the home yard, especially for planting fruits. Overall, a series of community empowerment activities through planting fruits in order to optimize the use of the home yard has given positive impact on the community. Appropriate cultivation techniques will provide benefits to society by increasing crop productivity. The product can be consumed or sold and participate in protecting the environment so that it remains sustainable. The enthusiasm of community was the evidence of their high curiosity and indicator of the successfulness of this activity.